Implementasi Teknologi sebagai Mitra Edukasi Anak Usia Dini dan Usia Sekolah Dasar - Ummy Kalsum; Meilinda Meilinda; Mega Wahyuni; Alfino Fathin Z (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The use of technology in early childhood and elementary education is becoming increasingly important in the digital era. This study aims to evaluate the effectiveness of educational games as an interactive learning medium to increase the interest and motivation of elementary school students. This activity was carried out by the KKM group 95 team from Bina Bangsa University on 43 fourth-grade students at Bayak Public Elementary School. The research method used a descriptive quantitative approach through a pre-test and post-test using a Google Form questionnaire. The educational games were developed through the Educaplay platform, which provides various features such as interactive quizzes, crosswords, and picture-matching games. Prior to the intervention, observations were conducted on student learning behavior in the classroom. The results of the initial observations indicated that most students showed little interest in conventional, monotonous learning methods. Therefore, a more engaging approach involving active student participation was needed to rekindle their enthusiasm for learning. During the activity, students were very enthusiastic in participating in the educational games presented. The classroom atmosphere became more lively, and students were seen working together and showing a high curiosity about the material presented through the games. After using the educational games for several sessions, a post-test was conducted to measure changes in students' interest and motivation to learn. Preliminary data analysis results indicate an increase in student interest and motivation scores after participating in educational game-based learning. This indicates that interactive, technology-based approaches have strong potential to improve learning effectiveness at the elementary school level. This study recommends that teachers actively integrate interactive technology into the teaching and learning process. In addition to increasing student engagement, the use of media such as Educaplay can also adapt learning to the digital-native characteristics of today's generation of students.